Effects of tiletamine/zolazepam-romifidine-atropine in ocelots (Leopardus pardalis) - Selmi, André L.; Figueiredo, Juliana P.; Mendes, Guilherme M.; Lins, Bruno T. [UNESP] (Elsevier, 2004)
Objectives: To evaluate the effects of a combination of tiletamine-zolazepam-romifidine-atropine in ocelots. Design: Prospective experimental trial. Animals: Eight captive adult ocelots (three females and five males). Methods: Calculated doses of tiletamine-zolazepam (3.75 mg kg -1), romifidine (50 μg kg-1) and atropine (0.04 mg kg-1) were administered intramuscularly. After immobilization, animals were weighed and the real doses determined. Heart rate, respiratory frequency, noninvasive systolic, diastolic, and mean arterial pressure, arterial oxygen hemoglobin saturation, and rectal temperature were measured. Data were analyzed by means of ANOVA for repeated measures, followed by the Tukey test to compare values over time. Results: Doses administered were 3.4 ± 0.6 mg kg-1 of tiletamine-zolazepam, 0.04 ± 7.0 mg kg-1 of romifidine, and 0.03 ± 0.007 mg kg-1 of atropine. The mean time to recumbency and duration of immobilization were 7.0 ± 4.5 and 109.2 ± 27.9 minutes, respectively. The median times to standing and walking were 52.3 [0-90] and 2.3 [0-69.3] minutes, respectively. A decrease in heart rate was observed 45 minutes following drug administration. Arterial blood pressure was maintained during the study. Conclusions and clinical relevance: This protocol produced good immobilization in ocelots with minimal changes over time in cardiovascular parameters.
Keywords: Dissociative anesthesia; Ocelots; Romifidine; Tiletamine; Zolazepam; atropine; romifidine; telazol; anesthetic agent; imidazole derivative; oxygen; tiletamine; zolazepam; analysis of variance; anesthesia; arterial oxygen saturation; arterial pressure; breathing rate; calculation; cardiovascular parameters; comparative study; data analysis; Felidae; female; heart rate; immobilization; male; mean arterial pressure; measurement; nonhuman; rectum temperature; animal; animal disease; blood; blood pressure; breathing; Carnivora; clinical trial; drug effect; intramuscular drug administration; muscle relaxation; physiology; prospective study; Anesthetics, Dissociative; Animals; Atropine; Blood Pressure; Female; Heart Rate; Imidazoles; Injections, Intramuscular; Male; Muscle Relaxation; Oxygen; Prospective Studies; Respiration